ETIKA MAHASISWA DALAM BERKOMUNIKASI DENGAN DOSEN MENGGUNAKAN APLIKASI WHATSAPP - Dikdik Febianto; Firli Nur Fadhillah; Ghani Wiharlan; Mugia Rizky Nugraha (IKIP Siliwangi, 2019)
Increasingly sophisticated communication tools are considered as one of the triggers for problems related to ethics in communication. Contacting lecturers through a text message application in the form of WhatsApp for academic purposes is a necessity so it is commonplace to do so. The content and language style raises new problems with regard to student ethics in contacting lecturers, for example students who do not include names, use language that the lecturer cannot understand, contact outside of working hours, and sentences that are not polite to read. The purpose of this research is to know and understand the ethics of students when communicating with lecturers, especially in the use of WhatsApp. This research uses a descriptive qualitative approach. Data collection using semi-structured interview techniques. The results showed that initial attitudes, information, and moral norms had a lot of influence on the way, language, and changes for students when contacting lecturers through the WhatsApp application.Keywords: Ethics, Whatsapp Application